Mitigação da produção de metano em cabras leiteiras com dietas contendo óleos de plantas do cerrado - Souza, Luana Magna de (2019)
Ruminants contribute to the emissions of methane (CH4), carbon dioxide (CO2) and nitrous oxide (N2O) to the atmosphere. Thus, it is necessary to establish feeding strategies for reducing the emission of greenhouse gases by ruminants as the inclusion of lipid supplements. For this purpose, this study aimed to evaluate the effect of including plant oils from the Cerrado on methane mitigation on dairy goats. The experiment was developed at the Federal Institute of Education Science and Technology of Maranhão, belonging to the Campus Caxias - MA. Five crossbred Saanen goats were used, weighing 31 ± 2.75 kg BW and distributed in a 5 x 5 Latin square design for 125 days. The experiment was divided into five periods of 25 days, being 20 days for adaptation and 5 days for data collection. The treatments consisted of control diet and 4 diets with the inclusion of vegetable oils in 3.5% of DM, being the oils: Macaúba, Pequi, Babaçue Buriti. Dry matter intake was not influenced by the addition of vegetable oils. There was a significant effect on the ether extract intake (P < 0.05), with a minimum value of 34.71 g / day and a maximum of 67.72 g / day. For the apparent digestibility coefficient of ether extract higher values (P < 0.05) were observed for goats in treatments with the inclusion of vegetable oil sources when compared to the control. There was no difference (P > 0.05) in ruminal ammonia nitrogen (N-NH3) and acetate, propionate and butyrate concentrations between treatments. Methane gas (CH4) production in g/day, kg/year, differ (P < 0.05) between the evaluated diets. The inclusion of 3.5% of Macaúba, Pequi, Babaçu and Buriti oils can be included in dairy goats feed, as it has no negative effect on intake, digestibility and ruminal parameters reducing the emission of enteric methane gas to the atmosphere.